ANALISIS EFEKTIVITAS IKLAN TV SIRUP MARKISA DENGAN PENDEKATAN EPIC MODEL PT. MAJUJAYA POHON PINANG PADA KONSUMEN SWALAYAN MACAM YAOHAN MERAK JINGGA MEDAN - Yet, Sian; Ginting, Paham (Jurnal Ekonomi Modernisasi, 2013)
Present competition of syrup business becomes tighter in terms of product quality, promotion, price and services provided. With many syrup product competing in the market, the management ofÂ  company is required to be more accurate in determining the strategy used to win the competition. PT. MajuJaya PohonPinang was chosen to be the object of study because this company has applied various strategies in marketing their products and one of them is through advertisement. Therefore, it needs a follow up to find out how effective the advertisement of Pohon Pinang Markisa Syrup related to the buying decision. The purpose of this quantitive descriptive explanatory survey study conducted at PT. MajuJaya PohonPinang Macan Yaohan Supermarket Merak Jingga Medan was to find out and analyze the effectiveness of Markisa Syrup commercial advertisement viewed from EPIC (Empathy, Persuasion, Impact, and Communication) dimensions and to find out the effectiveness and to partiality analyze the EPIC dimension using the theory of marketing management related to advertisement. Â The population of this study was the consumers of Macan Yaohan Supermarket Merak Jingga Medan and 100 of them were selected to be respondents for this study. The data obtained were analyzed through univariate analysis with T-test. The result of this study showed that simultaneously the variable of Markisa Syrup TV Commercial Advertisement viewed based on the EPIC model was effective. Partially, persuasion was the most dominant variable of the effectiveness of Markisa Syrup TV Commercial Advertisement